Peran Bimbingan Pranikah melalui Badan Penasihatan Pembinaan dan Pelestarian Perkawinan (BP4) di Cijeungjing Ciamis - Ayi Ishak Sholih Muchtar; Imas Umi Hani; Yusuf Sabanda (Istinbath | Jurnal Penelitian Hukum Islam, 2020)
Everyone who enters the gate of married life through marriage certainly wants the creation of a family or a happy, prosperous, and spiritual home and to obtain the salvation of life in the world and later in life. From this happy, prosperous family will come to be a harmonious, peaceful and just society of material and spiritual prosperity. This family and community life is the goal and goal of national development. In order for these ideals and goals to be carried out with the best, then the husband and wife who play a major role in creating a happy family prosperous, need to increase knowledge or education about how to foster family life in accordance with religious guidance and the provision of community life, expected every family member especially the husband and wife able to create the stability of household life filled with tranquility and peace.